2020
DOI: 10.33258/birle.v3i4.1492
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate and Postgraduate Education During Lockdown Due to COVID-19 Pandemic in Bangladesh

Abstract: In Bangladesh like the other nations around the world, the educational sector is highly affected due to COVID-19 lockdown. To know the overall picture of higher education during this lockdown and the perception of online education this study is conducted on 948 students. Our study findings show that around 73.7% of the students were involved in online education. 85.1% of the students used android mobile phones for attending online education and most (70.7%) of the respondents faced poor internet connection. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
0
0
Order By: Relevance
“…Studies on COVID-19 ERT in Bangladesh revealed that the major impediment to teaching online was inadequate infrastructural support required for virtual classrooms (Ahmed, 2021;Bashir et al, 2021;Dewan et al, 2022;Farhana et al, 2020;Khan et al, 2020Khan et al, , 2021Khan et al, , 2021aKhan et al, , 2023Mannan et al, 2020;Rafi que, 2023). These challenges included: a lack of access to devices and technologies, lack of access to the Internet, unstable and unreliable connections, and high Internet data costs.…”
Section: Nelta Infrastructural Issues and Pedagogical Challengesmentioning
confidence: 99%
“…Studies on COVID-19 ERT in Bangladesh revealed that the major impediment to teaching online was inadequate infrastructural support required for virtual classrooms (Ahmed, 2021;Bashir et al, 2021;Dewan et al, 2022;Farhana et al, 2020;Khan et al, 2020Khan et al, , 2021Khan et al, , 2021aKhan et al, , 2023Mannan et al, 2020;Rafi que, 2023). These challenges included: a lack of access to devices and technologies, lack of access to the Internet, unstable and unreliable connections, and high Internet data costs.…”
Section: Nelta Infrastructural Issues and Pedagogical Challengesmentioning
confidence: 99%